2020
DOI: 10.20473/jipk.v12i2.19723
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Research: Utilization of Gourami Fish Bone Flour (Osphronemus gouramy) in Making Calcium Dumplings

Abstract: HighlightKnowing the amount of daily calcium neededKnowing utilization of fish bone meal and its processed productsAnalysis of the most preferred types of food and fish speciesAbstractGourami (Osphronemus gouramy) is a type of freshwater fish native to Indonesia that is widely preferred, and has high economic value so that production per year increases. Increasing the amount of fish production will result in an increased amount of fish bone waste. However, the processing of gourami in general is still limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Gouramy (Osphronemus goramy) is a type of freshwater fish native to Indonesia that is widely preferred with high market demand, and selling price so that production per year increases [1,2]. Gouramy is very popular with the community, but its production is still quite low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gouramy (Osphronemus goramy) is a type of freshwater fish native to Indonesia that is widely preferred with high market demand, and selling price so that production per year increases [1,2]. Gouramy is very popular with the community, but its production is still quite low.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the maintenance period of gouramy is quite long. One of the efforts that can be done to increase production is to carry out intensive hatchery efforts [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have been conducted regarding calcium or hydroxyapatite extraction from fish bones of various species: tilapia (Abdullah et al, 2020), gourami (Handayani et al, 2019), yellowfin tuna (Nemati et al, 2017), skipjack tuna (Wardani et al, 2020), and Spanish mackerel (Anggresani et al, 2021). All of these studies, results cannot be categorized as nano-calcium because the particle size was bigger than 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Idowu et al [3] showed that salmon bone powder contained 25-37 % Ca, 15-17% of P, 0.3-0.7% of Mg, and 0.3-1 % of Na. All these nutrients in fishbone have prompted research into developing calcium-fortified food products, such as donut [4,5], crackers [5,6], cookies [7], and surimi IOP Publishing doi:10.1088/1755-1315/1119/1/012037 2 [8]. In addition, we require Ca as an essential micronutrient for human metabolism to prevent osteoporosis, rickets, epilepsy, and anaemia in our daily diet [1].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, using a solvent in fishbone extraction should be avoided for food safety reasons. Previous studies of fishbone powder using physical treatments were used many methods such as wet bead mill, speed homogenizer, grinder, blender, steam explosion, and superfine grinding [7,8,10,12,14,15]. Besides all these physical treatments, temperature and sonication are also known to affect structure properties and particle size reduction [16,17].…”
Section: Introductionmentioning
confidence: 99%